PENGEMBANGAN MULTIMEDIA PEMBELAJARAN PADA MATA KULIAH PENELITIAN TINDAKAN KELAS (PTK) DI UPBJJ – UT MEDAN - ASNAH SAID; HERNAWATY . (Jurnal Teknologi Pendidikan (JTP), 2012)
Abstract: The Classroom Action Research (PTK) is one of many other subjects found in educational program curriculum of Open University, either in Basic Education (Pendas) or Non-Basic Education (Non Pendas). The subject plays an important role in accelerating learning quality carried out by teachers. Through this subject, teachers are encouraged to perform a substantive action by understanding learning matters occuring at the time of teaching while involving in recovering and changing process. In this case, a teacher owns possibilities to carry out any changes in order to renew and improve the learning process in accordance with the real condition encountered in the class. In order to optimalize the process and learning output in the subject of the Classroom Action Research, the existence of multimedia learning is very necessary to complete printed learning materials (module) of PTK. Therefore, a research with Research and Development (R&D) method is conducted to yield a product in the form of multimedia learning as a completion for printed materials in the subject of PTK. The application of PTK learning is made through a software of Adobe Flash CS3 Professional. Besides, the Adobe Photoshop CS3 is also used to make pictures. This application is able to work with Flash Player. The aim of learning with this multimedia is to assist students to learn PTK easily and to make the learning interesting and fun as well as to activate them to learn independently. In addition, this application is also able to help tutors convey materials in PTK module, especially those in Modul 1 dan 2. The developed CD learning is claimed appropriate to use through a proper test carried out by the experts of Materials and Media. After being claimed appropriate to use, the effectivity of the CD learning is examined resulting in the improvement of learning output of about 30% in average.   Keywords: Classroom Action Research, Multimedia, Research and Development.